Reliability of the evaluation of humanoid animation as a visualizing tool in hip-hop dance - Sato, N.; Hopper, L. S. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to determine the reliability of the evaluation the humanoid animation by comparing the intra and inter-rater reliability between humanoid animation and stick figure animation of hip-hop dance. The humanoid animation and the stick figure animation were created using motion capture data from 16 hip-hop dancers. Five judges were asked to evaluate the 32 dance trials and they were not informed that they were repeating an evaluation. The intra-class correlation coefficient of the humanoid animation demonstrated very high reliability and was higher than the stick figure animation. There was no difference between the animations in the inter-class correlation coefficient. Humanoid animation may provide a more reliable method for the evaluation of dance movements as a feedback tool.